1999
DOI: 10.2135/cropsci1999.3961815x
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Root Chicory, Jerusalem Artichoke, and Sugarbeet in Stress and Nonstress Environments

Abstract: the traditional classification, according to the primary storage carbohydrate, into sucrose-, fructan-, and starch-Introduction of the fructan crops root chicory (Cichorium intybus crops, is becoming increasingly inappropriate. A recent L.; RC) and Jerusalem artichoke (Helianthus tuberosus L.; JA) into example is the creation of a fructan beet through inagricultural production systems is desirable to diversify crop rotation. Field experiments were conducted to compare the agronomic perfor-serting into sugarbee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 11 publications
8
41
1
2
Order By: Relevance
“…In general, plants allocate more biomass to the roots when growing under nitrogen deficiency (Lambers et al, 1998). In Cichorium intybus a low shoot: root ratio is induced by nitrogen deficiency in order to produce fructan rich tuberous roots (Améziane et al, 1997b;Schittenhelm, 1999). In the present study a similar effect was observed (figure 2).…”
Section: Discussionsupporting
confidence: 79%
“…In general, plants allocate more biomass to the roots when growing under nitrogen deficiency (Lambers et al, 1998). In Cichorium intybus a low shoot: root ratio is induced by nitrogen deficiency in order to produce fructan rich tuberous roots (Améziane et al, 1997b;Schittenhelm, 1999). In the present study a similar effect was observed (figure 2).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies were conducted to determine the effects of water stress on tuber yield and biomass of Jerusalem artichoke in both temperate (Conde et al, 1991;Losavio et al, 1997;Schittenhelm, 1999;Monti et al, 2005;Liu et al, 2012) and tropic regions (Ruttanaprasert et al, 2014). However, these previous studies did not focus on determining the effects of soil moisture content on tuber dry weight and total biomass (including root mass) of Jerusalem artichoke with different levels of drought resistance.…”
Section: Discussionmentioning
confidence: 99%
“…tolerant to drought should be the best long-term solution to the problem. Effects of drought stress on tuber dry weight, biomass (Conde et al, 1991;Losavio et al, 1997;Schittenhelm, 1999;Monti et al, 2005;Liu et al, 2012;Ruttanaprasert et al, 2014) harvest index (Conde et al, 1991;Ruttanaprasert et al, 2015) and water use efficiency (Conde et al, 1991;Janket et al, 2013) of Jerusalem artichoke has been reported in several studies. In temperate regions, drought stress reduced Jerusalem artichoke tuber yield by 20% (Conde et al, 1991;Losavio et al, 1997) but increased water use efficiency by 7-35% and harvest index by 21% (Conde et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A formação de rizoma em Lotus corniculatus é induzida no outono, pelas condições de baixa temperatura (Kallenbach et al 2001). O teor de umidade é outro fator que influencia a formação de órgãos subterrâneos (Rizzini 1965;Schittenhelm 1999;Williams et al 2002). Aleixo & Válio (1976) observaram que gemas de tubérculos de Cyperus rotundus não se desenvolveram quando foram mantidas em condição de desidratação, permanecendo quiescente.…”
Section: Introductionunclassified